Validade do estudo contrastado para o diagnóstico de alterações da bolsa do navicular - Teichmann, Cristiane Elise (2005)
The navicular disease represents a degenerative disease of the navicular bone and associated structures. The diagnosis is based on history, clinical signs and nerve or nerve or joint blocks in addition to abnormalities seen in the radiographs. In order to evaluate the relationship of the radiographs findings and histology lesions inside the navicular bursa and adjacent structures 62 distal limb specimen were used in this study. The specimens were radiographed (dorso-palmar, lateral and skyline views) and a bursagram was performed. Then the specimens were processed to harvest the navicular bone and adjacent structures for histopathology. The results of this study showed that the positive predictivity was 71%. Considering only lesions seen at the bursagram the positive predictivity was 50%